Optimization of the fermentation process through ELF magnetic field radiation and its effect on Cascara Caffeine - Nurul Komaria; Suratno Suratno; Sudarti Sudarti; Dafik Dafik (Caspian Journal of Environmental Sciences)
Coffee is in high demand on the global market due to its distinctive scent. Part of the coffee is coffee waste which needs be processed to increase its economic worth. One of the efforts made is to vary the fermentation process with the ELF magnetic field on cascara. Thus, the purpose of this study was to optimize the effect of the ELF magnetic field fermentation process on cascara robusta coffee to reduce caffeine content. We utilized an experimental study. The results demonstrated that a magnetic field affected the levels of caffeine, trigonellin, and bacteria during the fermentation process. Caffeine and trigonelin test results for each treatment in the control and treatment groups.